Ecotoxicological studies of metabolites produced by two Brazilian cyanobacterial strains - Torres, Mariana de Almeida (2023)
Cyanobacterial blooms affect freshwater ecosystems across the globe, and one major concern relates to their structurally diverse and bioactive metabolites not limited to known toxins such as microcystins (MC). Yet, the ecotoxicological risks associated with these co-produced metabolites remain mostly unknown. In this study, we assessed metabolites from two Brazilian Microcystis strains, the microcystinproducer MIRS-04 and the non-producer NPCD-01, by LC-HRMS/MS using CyanoMetDB (a comprehensive database of cyanobacterial secondary metabolites) for the suspect screening. Ecotoxicological studies were conducted with the freshwater organisms Thamnocephalus platyurus (fairy shrimp) and Danio rerio (zebrafish) in embryo-larval stage. The survival and locomotor (swimming) behaviour of the two species were monitored after exposure to HPLC-semi-purified fractions of the cyanobacterial extracts. For the zebrafish embryos, morphological alterations and cardiovascular functions of 5-day-old larvae were also analysed. The whole cyanobacterial extract (pooled HPLC fractions) from the MC-producer and nonproducer pointed to acute dose-dependent toxicity in both model species tested. For the fairy shrimp, acute effect on survival was also observed for the HPLC-fraction of the MC-producer containing the cyanopeptolin micropeptin K139, and the apolar fractions revealed to be the main contributors to the acute toxicity of the microcystinfree extract. Additionally, sublethal effects (represented as reduced mobility) was also observed on the microcrustaceans exposed to the pooled, micropeptindominated (MIRS-04) and apolar fractions (NPCD-01). In the zebrafish embryos, likewise, mortality was recorded after 120h of exposure to the pooled fractions of both strains, the micropeptin-dominated fraction of the MIRS-04 strain, and apolar fractions of the NPCD-01. In addition, oedemas of the pericardial region were observed in larvae exposed to the HPLC-fractions dominated by the microginin nostoginin BN741 (non-producer) and micropeptin K139 (MC-producer). Our results further add to the growing evidence of toxicity of cyanobacterial metabolites other than microcystins.